Pengaruh Pembelajaran Mendalam Terhadap Kemampuan Menulis Kreatif di Era Teknologi Digital - Andi Nayla Azzahra; Sri Anggini; Ariqah Upairah; Anita Candra Dewi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Creative writing skills in the era of digital disruption face challenges in the form of shallow learning and dependence on technology automation. This study aims to analyze the effect of implementing a deep learning approach on enhancing students' creative writing skills and how this strategy can maintain the originality of works amidst the widespread use of digital technology. This study uses a descriptive qualitative method. Data were collected through in-depth interviews with lecturers and students, participatory observation in the learning process, and document analysis of creative writing drafts. Data analysis was conducted qualitatively in stages, including data reduction, data presentation, and drawing conclusions. Research results indicate that the implementation of deep learning triggers a shift in students' creative processes from superficial writing toward the synthesis of more complex meanings. Digital technology transforms its role from merely a typing aid into a thinking partner that expands the reach of imagination. This approach significantly strengthens the originality and character of students' writing, preventing it from being trapped in the standardization of digital content. The conclusion of this study affirms that deep learning is an effective pedagogical strategy to transform creative writing skills into higher-quality, reflective, and adaptive abilities in response to technological developments.